Symbol Matters: A Sequential Mediation Model in Examining the Impact of Product Design with Buddhist Symbols on Charitable Donation Intentions - Qin, Zhenzhen (Religions, 2022)
Though religion-informed charitable behavior has gained much academic attention recently, there is an ambiguous relationship between individual donation intention and Buddhist determinants. Drawing on the theories of reasoned action and product semantics, this study tries to examine the effects of product design with Buddhist symbols on individual charitable donation behavior and the underlying mechanism. Some studies have argued for the positive effects of religious symbols on people’s behavioral reactions; however, limited prior research has addressed the impact of a touchable product, such as a donation box, on people’s charitable donation intentions from the perspective of Buddhism. The current study statistically shows that donation boxes with Buddhist symbols could significantly improve people’s charitable donation intention through two sequential mediators, namely, their perceived religiosity and product attitude. The study provides both theoretical contributions and practical implications for future research.